DNA binding, BSA interaction and in-vitro antimicrobial studies of Cu(II), Co(III), Ni(II) and VO(IV) complexes with a new Schiff base. Issue 1 (1st January 2020) - Sharma, Disha; Revanasiddappa, Hosakere D.; Jayalakshmi, Basavegowda
ABSTRACT: A new bidentate (E)-2-((3-(benzyloxypyridinylimino) methyl)-6-methoxyphenol (L) and its complexes such as [Cu(L)2 ] (C1), [Cu(L)(Phen)] (C2), [Co(L)2 ] (C3), [Co(L)(Phen)] (C4), [Ni(L)2 ] (C5), [Ni(L)(Phen)] (C6), [VO(L)2 ] (C7) and [VO(L)(Phen)] (C8), (L = Schiff base derived from 2-amino-3-benzyloxypyridine and 3-methoxy salicylaldehyde, Phen = 1, 10-phenanthroline) were synthesized and the prepared complexes were characterized by different analytical techniques elemental analysis, magnetic moment, molar conductance, infrared spectra, 1 H and 13 C NMR, mass, electronic absorption and Thermogravimetric Analysis (TGA). Electron Paramagnetic Resonance (EPR) spectrum of Cu(II) and VO(IV) complexes are studied. The synthesized compounds C1–C8 were primarily screened for their in vitro anti-microbial activities against gram positive, gram negative bacteria and fungi. The remarkable antimicrobial activity results from complexes C-C8. The interaction between the newly prepared ligand and Cu(II), Co(III), Ni(II) and VO(IV) complexes with calf‐thymus DNA (CT‐DNA) was achieved by absorption, fluorescence, and viscosity measurements. The binding of metal complexes with BSA (bovine serum albumin) was reported by the multi spectroscopic methods. The results illustrated that the C1–C8 complexes can significantly interact with the DNA via intercalation mode and a static quenching is reported for BSA. As a result of this the deformity in secondary structure of BSA occurs.